2003
DOI: 10.1128/jb.185.18.5500-5507.2003
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase III from the Hyperthermophilic Archaeon Sulfolobus solfataricus with Specific DNA Cleavage Activity

Abstract: We report the production, purification, and characterization of a type IA DNA topoisomerase, previously designated topoisomerase I, from the hyperthermophilic archaeon Sulfolobus solfataricus. Topoisomerases are ubiquitous enzymes that participate in nearly all cellular activities involving DNA transactions (5, 31). Based on their catalytic mechanisms, topoisomerases are classified into two classes: type I enzymes, which generate a transient break on one DNA strand to allow the passage of the intact strand wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 38 publications
3
35
1
Order By: Relevance
“…Sso topo III is sequence-specific in oligonucleotide cleavage, showing the strictest requirement for bases at positions −6 to −3 (Dai et al, 2003). In this study, we found that complementarity to a region from −6 to +2 in the C strand was important for annealing-promoted religation of the cleaved strand by the enzyme.…”
Section: Annealing-promoted Religation Tolerates Mismatches Near the mentioning
confidence: 57%
See 4 more Smart Citations
“…Sso topo III is sequence-specific in oligonucleotide cleavage, showing the strictest requirement for bases at positions −6 to −3 (Dai et al, 2003). In this study, we found that complementarity to a region from −6 to +2 in the C strand was important for annealing-promoted religation of the cleaved strand by the enzyme.…”
Section: Annealing-promoted Religation Tolerates Mismatches Near the mentioning
confidence: 57%
“…It was shown in the previous study that oligonucleotide cleavage by Sso topo III was not detectable at 0 ° C, very low but measurable at 37 ° C, and peaked at 65-75 ° C (Dai et al ., 2003). However, this pattern of temperature dependence was subsequently found to result from nucleic acid contamination in the enzyme preparation.…”
Section: The Equilibrium Between Cleavage and Religation Of Oligonuclmentioning
confidence: 99%
See 3 more Smart Citations